Peripheral Realisms: The Regional and Transnational Dynamic of Contemporary Brazilian Cinema (Cinéma & Cie. Film and Media Studies Journal, 2013)
This article concerns the redefinition of realism from the perspective of its impact on contemporary Brazilian cinematography, commenting on and analyzing the stylistic strategies of filmmakers who are situated at the margins of the traditional centers of film production in Brazil. My focus will be on films from the Northeast, and even more specifically those produced in the state of Pernambuco from the late 2000s. For instance, a brief overview of the most recent production by directors such as Gabriel Mascaro, Marcelo Pedroso, Marcelo Lordello and especially Kleber Mendonça Filho shows that this “realist turn” breaks with a naturalist and caricatured tradition of filmmaking in Pernambuco (as it is the case of the previous regional cycle in the state). A more detailed analysis of Mendonça Filho’s Neighbouring Sounds (2012) will be helpful to demonstrate under what conditions this rupture occurred and how it is related with the emergence of a peripheral aesthetics of realism.